Nutrient Profiles of Thai Cuisine: A Comprehensive Survey and Computation using Nutrient Analysis Software - Sarachantapong, Pakpadsorn; Sopawong, Pornnutcha; Kriengsinyos, Wantanee; Sridonpai, Pimnapanut; Pachotikarn, Chanida (Journal of Nutrition Association of Thailand (Online), 2025)
This study aimed to categorize Thai cooked food and calculate the nutrient profile of Thai side dishes and combined meals, as grounded in Thai food culture. This observational descriptive study collected and calculated the nutritional value of recipes from cookbooks, online media, and regular diets prepared in hospital settings. Energy (kcal), protein (g), total fat (g), vegetables (g), added sugar (g), and sodium (mg) were evaluated per common serving, which was defined by weighing food that was served in hospital. Differences among categories were tested using the Mann Whitney U-test with a p-value ≤ 0.05. Categories were separated if nutrient profile showed a significant difference. Two meal patterns were created, namely, a combination of one staple and two side dishes as well as a single dish set. The nutrient profiles of these two meal patterns were compared to the nutrient target values (NTVs). A total of 2,347 recipes were analyzed and classified into 14 categories: 11 side dishes, 2 single dishes, and 1 staple dish. Categories were distinguished based on at least one nutrient differing significantly from others (p-value < 0.05 for all pairwise comparisons). A total of 57 possible model meals with varying nutrient profiles were assessed. Some model meals met the NTVs for energy, protein, fat, vegetables, and added sugar, while all meals exceeded the NTV for sodium. This study highlighted the diversity of Thai food, with each category exhibiting unique characteristics that may impede a complete nutrition profile. However, good side dish combinations can enhance meal quality to meet NTVs. Consequently, developing recipes that maintain traditional Thai flavors while enhancing nutritional quality and promoting healthy eating has the most potential for optimizing consumer health.